Tipologi Abreviasi dan Akronim: Titik Pijak Awal Pemanfaatan Semantik dalam Penyusunan Kamus Bahasa Indonesia - Khoirunnisa, Krismonika; Sumarlam, Sumarlam; Nugroho, Miftah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
Indonesian has many vocabularies which have developed more or less according to the user community and their needs. With the existence of an Indonesian dictionary that contains vocabulary and meanings that serve as guidelines, standardization of vocabulary in the KBBI and requires scientific negotiation. Through semantic science which is the basis for its compilation and standardization, with the present dictionary presentation, vocabulary and meaning will be easier to understand. The type of research used in this study is a qualitative research using descriptive analysis. This qualitative method is used by researchers to analyze the data findings. The data’s source in this study is from KBBI V (online). The dictionary will be analyzed for its elements of abbreviations and acronyms. Analysis this study was carried out descriptively which later was expected to be able to find the characteristics, properties, and functions through the selection of the required data. The results of this study found that there are several abbreviations and acronyms found in the KBBI (online). Abbreviations and acronyms found are seen from the process of formation, form, and function. Another existence found by researchers is the use of abbreviations and acronyms as research that can enrich and vocabulary development.